Mechanical, physical and morphological properties of arrowroot starch reinforced arrowroot nanocrystalline cellulose biopolymer nanocomposites film - Firdaus, A. H.M.; Sapuan, S. M.; Siddiqui, Vasi Uddin; Atiqah, A.; Zainudin, E. S. (Elsevier, 2025)
Extensive studies have systematically uncovered the key mechanisms by which nanocellulose integrates into various starch-based botanical matrices. This research aims to investigate the mechanical, physical, and morphological properties of nanocellulose arrowroot starch reinforced arrowroot nanocrystalline cellulose (AS/ANCC) biopolymer nanocomposites. The extraction of arrowroot nanocellulose ANCC was done by acid hydrolysis method using sulfuric acid with a concentration of 55 %. The solution casting method was performed to prepare the arrowroot starch (AS) biopolymer film with different ANCC loadings of (0,1,3, 5 and 10 %wt) utilizing a combined 30 % glycerol and sorbitol as a plasticizer. The incorporation of ANCC consistently increased film thickness and density, indicating a filler effect. Water absorption behavior varied, generally increasing with ANCC content due to its hydrophilic nature. Mechanically, ANCC significantly enhanced both tensile strength and elongation at break, with an optimal loading observed at 3 %, though it concurrently reduced Young's Modulus. Thermally, TGA results showed that while the onset of main degradation might slightly decrease, char yield significantly increased with higher ANCC loadings, indicating improved thermal stability through char formation. Chemical analyses (FTIR, Raman) confirmed ANCC's successful integration and its influence on molecular structure, supported by XRD data revealing increasing crystallinity with higher ANCC content. Overall, the incorporation of ANCC significantly enhanced AS films, offering improved mechanical strength, flexibility, and thermal stability of the biopolymer nanocomposite films.